The Forest of Unintended Consequences: Anthropogenic Actions Trigger the Rise and Fall of Black Cherry. (17th February 2021) - Royo, Alejandro A; Vickers, Lance A; Long, Robert P; Ristau, Todd E; Stoleson, Scott H; Stout, Susan L
Abstract: The twentieth century confluence of clear-cutting, deer overabundance, and rising nitrogen deposition favored dominance by the shade-intolerant, unpalatable, and nitrogen-demanding black cherry (Prunus serotina) throughout the Allegheny Plateau of the eastern United States. The abundance of this species conferred unique and valuable ecological and economic benefits that shaped regional biodiversity and societies. Sustaining these values is increasingly difficult because black cherry, seemingly inexplicably, has experienced diminished establishment, growth, and survival in the twenty-first century. In the present article, we chronicle the change and assess underlying drivers through a literature review and new analyses. We found negative plant–soil microbial feedback loops and lowered nitrogen deposition are biologically, temporally, and geographically consistent with observed declines. The evidence suggests that black cherry dynamics are the unintended consequence of actions and policies ostensibly unconnected to forests. We suggest that these shifts are a bellwether of impending changes to forests, economies, and ownership patterns regionally and beyond.